Blocking the arsenic transportation from micro-polluted lake water to water spinach by in situ addition of titanyl sulfate. (20th January 2023) - Zhou, Juanjuan; Li, Dongqin; Li, Bingqian; Liu, Yanwei; Li, Huashou; Chen, Guikui; Qiu, Rongliang
Abstract: Water resource shortage and arsenic (As) water pollution are threatening human food security. Using As micro-polluted water for agricultural production may alleviate the water resource shortage situation after solving the As problem. In situ formed hydrous titanium oxide possesses much higher As immobilization potential than purchased TiO2 because of its higher specific surface area and more abundant active hydroxyl group, which is proposed to reduce the As uptake of aquatic vegetables planted in As micro-polluted water. Herein, TiOSO4 solution, which can hydrolyze into hydrous titanium oxide during dilution in water, was used as a new water amendment to realize in situ As immobilization in lake water (100 μg-As/L) during cultivation of water spinach. We found that TiOSO4 could immobilize trace level As with its dosage as the main factor influencing the efficiency through response surface analysis. A low dosage TiOSO4 treatment of 0.5 mg/L could reduce the As content in the edible part from 0.64 to 0.40 mg/kg, which satisfied the vegetable As standard of China (0.5 mg/kg). The shoot As content was negatively related to the used TiOSO4 dosage and could be further reduced to 0.16 mg-As/kg at a dosage of 4 mg/L TiOSO4, while the health risk index of eating water spinach could be reduced by 75% (from 1.6 to 0.4). Therefore, TiOSO4 is a useful in situ As immobilization reagent during cultivation of water spinach and may possibly be used in the production of other aquatic vegetables. In situ TiOSO4 treatment may be an effective and facile strategy for the agricultural utilization of As micro-polluted surface water, which can alleviate the shortage on safe agricultural water resource in the context of widespread water micro-pollution. Graphical abstract: Image 1 Highlights: TiOSO4 removed trace arsenic efficiently from lake water via coagulation. TiOSO4 -treated lake water was used for water spinach cultivation. TiOSO4 treatment did not affect the yield of water spinach. 4 mg/L TiOSO4 decreased As concentration in water spinach edible part by 75%. In situ TiOSO4 treatment is a facile strategy to utilize As micro-polluted water.